ICT and food security in Africa - Adeniran, Adebusuyi Isaac; Aristide, Djane Kabran (Cambridge Scholars Publishing, 2020)
This volume provides apt and timely insights into how a globalizing African society could use the array of opportunities that various applications of ICT offer to supply much-needed food sustainability for the people of Africa. Looking at the entire agricultural value chain, the book presents a viable empirical framework for engaging with ICT in processes of food production and distribution, especially for rural low-scale agriculturists. It also depicts how the platform of ICT could play a central role in making the larger continental-goal of sustainable food security a realistic projection. I.